유해성 단일물질들로 구성된 혼합물의 수서생태계 독성값 추정 - 김지현; Jihyun Kim; 안창효; Yongwoon Lee; 이용운; Seongjun Kim; 김성준; Kwonsub Lee; 이권섭; Jaechoon Lee; 이재춘; Seunghee Jin; et al. (환경분석과 독성보건, 2023)
The aquatic environment contains numerous mixtures of various combinations of hazardous single substances, and it is difficult to calculate the toxicity values of all mixtures by test methods. Therefore, the estimation method based on the UN-GHS model has been widely used. However, there are cases where the difference between the model estimate and the actual (test) value is large, indicating the need for research to reduce the uncertainty of the model. This study aims to develop a modified model that can solve the problems of the UN-GHS model, and to evaluate the applicability of the modified model through toxicity testing of mixtures. An acute Daphnia magna toxicity test was conducted according to the drug mixture exposure, and the difference between the toxicity test result and the model estimate was analyzed assuming that it was derived from the model uncertainty. The large difference between the UN-GHS model estimate and the test result was due to the toxicity weighting factor, determined by dividing the L(E)C50 of each single substance into interval values. Therefore, in this study, the existing model was improved by developing a modified model that assigns a toxicity weighting factor to the point value, rather than the interval value of L(E)C50 for each single substance. The estimate of the modified model showed an average difference of 16.7% from the toxicity test value, which was 3.9 times more accurate than the existing model (average 64.4%). Thus, the modified model can be a useful method for estimating the toxicity values of mixtures composed of single substances. KCI Citation Count: 0